2022
DOI: 10.3390/insects13030220
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trap Color on Catches of Monochamus galloprovincialis and Three Most Numerous Non-Target Insect Species

Abstract: Black pheromone-baited traps are commonly used for monitoring Monochamus galloprovincialis, a vector of Bursaphelenchus xylophilus, although few studies have been conducted on its response to color (black, white, and clear). The objective of our studies was to evaluate the attractiveness of different colors to M. galloprovincialis and non-target species: Spondylis buprestoides and predatory Thanasimus formicarius and T. femoralis. Laboratory tests of fifteen colors against immature and mature M. galloprovincia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…En el presente estudio, insectos fitófagos, como el chinche salivazo presente durante los muestreos dentro de las plantaciones, presentaron preferencia por el color de trampa verde y amarilla que son similares a la coloración de la planta hospedera, la caña de azúcar, relación que ha sido demostrada con estudios previos entre insectos, trampas y plantas hospederas (Sukovata et al, 2022) Las trampas pegajosas de colores han sido utilizadas en capturas de insectos de hortalizas de hojas, incluyendo lechuga (Lactuca sativa L.) y repollo (Brassica oleraceae var. capitata), para capturar plagas tales como trips (Thysanoptera), cigarritas (Hemiptera: Cicadellidae), pulgones (Hempiptera: Aphididade) y psílidos (Hempitera: Psyllidae), destacándose igualmente los colores de trampas amarillo y verde en la captura de insectos fitófagos (Bravo-Portocarrero et al, 2020), que es consistente con lo encontrado en este estudio.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En el presente estudio, insectos fitófagos, como el chinche salivazo presente durante los muestreos dentro de las plantaciones, presentaron preferencia por el color de trampa verde y amarilla que son similares a la coloración de la planta hospedera, la caña de azúcar, relación que ha sido demostrada con estudios previos entre insectos, trampas y plantas hospederas (Sukovata et al, 2022) Las trampas pegajosas de colores han sido utilizadas en capturas de insectos de hortalizas de hojas, incluyendo lechuga (Lactuca sativa L.) y repollo (Brassica oleraceae var. capitata), para capturar plagas tales como trips (Thysanoptera), cigarritas (Hemiptera: Cicadellidae), pulgones (Hempiptera: Aphididade) y psílidos (Hempitera: Psyllidae), destacándose igualmente los colores de trampas amarillo y verde en la captura de insectos fitófagos (Bravo-Portocarrero et al, 2020), que es consistente con lo encontrado en este estudio.…”
Section: Discussionunclassified
“…Estudios previos han demostrado que por ejemplo las trampas de color blanco pueden capturar el escarabajo longicornio Monochamus galloprovincialis Olivier (Coleoptera: Cerambycidae) pero además sus enemigos naturales (Sukovata et al, 2022), elemento que nos indica que el uso de diversos colores puede contribuir a conocer la biodiversidad de especies presentes dentro de un agroecosistema.…”
Section: Discussionunclassified
“…In the studies reported here, the dark green panel traps were much more effective than the transparent funnel traps. Papers published since our field studies were conducted have shown that trap colour can strongly affect the attractiveness of baited traps to longhorn beetles (Cavaletto, Faccoli, Marini, Spaethe, Giannone, et al, 2020; Sukovata et al, 2022). Similarly, C. mutillarius appears to be attracted by dark colours (Cavaletto, Faccoli, Marini, Spaethe, Magnani, & Rassati, 2020), while other clerid beetles were reported to be most attracted to unpainted white traps (Sukovata et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Papers published since our field studies were conducted have shown that trap colour can strongly affect the attractiveness of baited traps to longhorn beetles (Cavaletto, Faccoli, Marini, Spaethe, Giannone, et al, 2020; Sukovata et al, 2022). Similarly, C. mutillarius appears to be attracted by dark colours (Cavaletto, Faccoli, Marini, Spaethe, Magnani, & Rassati, 2020), while other clerid beetles were reported to be most attracted to unpainted white traps (Sukovata et al, 2022). The better performance of panel traps compared to funnel traps for most of the species might be explained by colour, or by other trap characteristics such as size and silhouette.…”
Section: Discussionmentioning
confidence: 99%
“…The three attractants had components in common of geranyl acetone, fuscumol acetate, fuscumol and monochamol, which are components of the pheromones of various species of the cerambycid subfamilies Spondylidinae and Lamiinae [ 27 , 28 , 29 ], 3-hydroxyhexan-2-one, 2-methyl-1-butanol, and anti -2,3-hexanediol, which are components of the pheromones of various species of the subfamily Cerambycinae [ 30 , 31 , 32 ], prionic acid, which is the sex pheromone of various species of the genus Prionus (Coleoptera: Cerambycidae: Prioninae) [ 33 ], and ethanol, which is released from infested trees [ 34 , 35 , 36 ], enhancing the attraction of wood-boring insects [ 37 , 38 ]. Attractant 3 additionally contained the components α-pinene, which is the kairomonic component released by host trees [ 39 ] and ipsenol, which is an aggregation pheromone of wood-boring insects of the subfamily Scolytinae (Curculionidae) [ 40 , 41 ]. Attractant 2 contained only α-pinene as an additional component.…”
Section: Methodsmentioning
confidence: 99%